PENGARUH REPUTASI KANTOR AKUNTAN PUBLIK PADA HUBUNGAN ANTARA OPINI AUDIT GOING CONCERN DAN AUDIT DELAY PADA AUDITOR SWITCHING - Sukadana, I Dewa Made; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2016)
This study was conducted to determine the effect on the relationship between the firm's reputation going concern audit opinion and audit delay in switching auditors. The population in this study are all companies listed on the Indonesia Stock Exchange in 2013-2014. The sampling method used is purposive sampling method. The number of samples used in this study is 42 companies. Data collection methods used in this study is a non-participant observation method. Data analysis techniques used to solve these problems, namely logistic regression analysis. Based on the results of analysis known that reception going concern audit opinion influences how the company conducts auditor switching, audit delay has no effect on the tendency of companies doing auditor switching, reputation of KAP strengthen the effect of going concern audit opinion on the trend of companies doing auditor switching, and the reputation of KAP weaken the influence of audit delay on the trend of companies doing auditor switching.
Keywords: going concern, audit delay, reputation of KAP, auditor switching